On the disposal of our convicts - McKenna, P. J. (Dublin Statistical Society, 1857)
It is especially irksome to find men of education and intelligence adopting, without consideration or enquiry, the opinions of newspaper writers, whose object in the present day seems to be to reflect public opinion rather than to instruct or inform it. The public is irritated, and justly so, by the outrages of the ticket-of-leave men in England; and I am quite prepared for their running away with the subject, and losing their senses in talking about it, with the first impulse of that irritation ; out that they should whirl along with them many who might fairly ?e expected to form sound conclusions, and to help in stemming the torrent, must be a matter of deep regret to all who have inquired into and take an interest in this subject. I consider it a duty to assist in setting the question fairly before the public, however small that assistance; and if, in stating my opinions and the reasons for those opinions, I should bring forward facts known to, many, arguments that may be common-place, and reasonings obvious on a moment's reflection, I shall hope to be forgiven.
Read 15th December, 1856
Keywords: Convicts; Prison service; Penal colonies; Penal servitude; Prisoners; 314.15